Gender equality in caregiver attendance for children with chronic diseases: a Swedish longitudinal observational study - Henrik Imberg; Marcus Svedberg; Linda Mark; Viktoria Mellqvist; Jens Michelsen; Kristel Björkman; Niklas Johansson (BMJ Public Health, 2025)
Objectives In countries at the forefront of gender equality policy, mothers still play a more pronounced role than fathers in the provision of parental care for their children. This study aimed to explore gender equality in attendance at doctor’s appointments among caregivers of children with chronic diseases before and after the introduction of video conference visits.Methods Children aged 0–17 years diagnosed with cystic fibrosis, inflammatory bowel disease, diabetes or a chronic neurological disease at Gothenburg’s and Lund’s paediatric hospitals were included. Data on caregiver attendance from 2019 to 2022 were retrospectively collected from medical records. Doctors’ appointments were categorised as in-person, telephone or video conference visits. Using mixed-effects models, we evaluated trends in parental attendance and assessed the associations between different types of appointments and gender equality in healthcare.Results A total of 347 participants were included between 2019 and 2022, resulting in 6134 appointments. Overall attendance rates were 74% for mothers and 44% for fathers, corresponding to a difference of 30%-points (95% CI 27% to 32%-points, p<0.001). Mothers had consistently higher attendance rates across all types of appointments (all p<0.05). The attendance gap between mothers and fathers remained similar over time, except for video conference visits where an increase in maternal attendance was observed (p<0.001) while paternal attendance remained constant (p=0.90). Video conference visits had higher joint attendance rates than in-person and telephone appointments (both p<0.001).Conclusion Mothers attended paediatric outpatient visits more frequently than fathers across all appointment types. The gender gap in attendance remained unchanged after the introduction of video conference visits, while the joint attendance increased. Future interventions should explore structural strategies to enhance gender equality in caregiver attendance.